(untitled) (REMUNOM, 2025)
Dental care for patients with HIV/AIDS is a challenging field that requires sensitivity and specific knowledge from dental surgeons. The immunosuppressed condition associated with the virus increases susceptibility to oral health problems, demanding specialized care. This study aimed to analyze the knowledge and practices of dental surgeons in the municipality of Araruna-PB regarding the care of patients with HIV/AIDS. This is a cross-sectional, descriptive, and quantitative study. Data were collected through structured questionnaires applied in public health units and private clinics, containing 37 items covering information on dental management, oral and ethical aspects, and biosafety practices adopted by the 22 dentists included in the sample. The data were analyzed using SPSS software version 25.0. The dental surgeons in the sample demonstrated satisfactory understanding of oral manifestations, dental management, and biosafety practices in the care of patients with HIV/AIDS. However, certain practices were identified as needing improvement, such as needle recapping, some ethical aspects, and knowledge about pre-exposure prophylaxis (PrEP). Dental surgeons in Araruna demonstrated a reasonable level of proficiency in the care of patients with HIV/AIDS, although further improvement is needed, highlighting the importance of continuing education to ensure more effective and humanized care.